Exploring the systemic impacts of urinary tract infection-specific antibiotic treatments on the gut microbiome, metabolome, and intestinal morphology in rats - Hao Guo; Xiang Zhou; Zhou Li; Junjie Zhi; Chaowei Fu; Xinwei Liu; Yufan Wu; Fengping Liu; Ninghan Feng (PeerJ)
The gut microbiota is a dynamic ecosystem that plays a crucial role in host metabolism, immune system regulation, and protection against pathogens. An imbalanced gut microbiota has been associated with various diseases such as inflammatory bowel disease, metabolic disorders, and autoimmune diseases. Antibiotic therapy can disrupt the balance of the microbiome, making it essential to understand the specific effects of these antibiotics on gut microbiota and related host function. This study aims to systematically investigate the impact of UTI-specific antibiotic treatment on the gut microbiota of rats. By analyzing changes in microbial composition and their effects on host metabolism and intestinal structure, we seek to provide new insights into the broader consequences of antibiotic intervention on host-microbiota interactions. The research findings indicate that antibiotic treatment leads to a significant disruption in microbial diversity and metabolic characteristics, as well as notable histological changes in the intestinal mucosa. These results highlight the need for cautious use of antibiotics, considering their extensive effects beyond antimicrobial activity. Future research should focus on strategies to mitigate these impacts, potentially through targeted antibiotic therapies or probiotics, to better balance treatment efficacy with health preservation.